Feminist theory and the Bible: interrogating the sources - Fuḳs, Ester (Feminist studies and sacred texts series, 2016)
Feminist approaches to the Hebrew Bible -- Biblical feminisms: knowledge, theory, and politics in the study of women in the Hebrew Bible -- The neo-liberal turn in feminist biblical studies -- Jephthah's daughter: a feminist postcolonial approach -- Women as prophets/women in prophets: gender, nation and discourse -- Intermarriage, gender, and nation in the Hebrew Bible